Innovation of Tarragon Leaves, Curry Leaves and Garlic Vine into Local Herbs - Rose De Beth Alonzo; Addrich A. Asaldo; Mark Angel P. Paclib; Mariel Pangilinan; Katrina A. Sarabia; Marcos Paolo M. Soriano (JURNAL GASTRONOMI INDONESIA, 2022)
This research focused on the innovation of Tarragon Leaves, Curry Leaves, and Garlic Vines for the purpose of utilizing some herbs that are mostly unnoticed in the Philippines but have culinary potentials. The process involved a careful selection of raw materials, drying, formulation, testing, packaging, and labeling. To come up with a fully organic and desirable flavor, formulations were tested and evaluated by 10 food experts to determine the product’s general acceptability in terms of its quality attributes. Paired T-test was used for data interpretation using SPSS. The results showed that the product yields 44 calories per 9 grams of serving with a very low moisture content of 6.24%, therefore proving that it is safe and not susceptible to microbial growth. The product can also last for a month at room temperature or longer under proper storage conditions. Sensory evaluation results revealed that based on general acceptability, TCG local herbs highly complements grilled chicken, beef, pork, and fish respectively with a mean rating of 8.0, 7.3, 7.2, and 6.2 wherein seasoned chicken was perceived as “like very much” and seasoned fish with “like slightly”. As careful steps were completed, this research made the innovation of organic and underutilized herbs possible.